The Concept of Reality as a Factor for the Development of Mental Disorders - Mikayelyan, Erik (Bulletin of Yerevan University E: Philosophy, Psychology, 2013)
Our attitude towards our mental condition depends on the fact if we find ourselves responsible for our mental conditions or if we think that those conditions are caused by some unknown power. Everyone has a concept of reality programming our mental and physical health. In case of mental disorders one deals with a conflict of two different concepts of the reality, i.e. this conflict may cause mental disorders. This means mental health presumes overall perception of the reality concept.